The Role Of The Medan Police In Law Enforcement Of Criminal Acts Of Narcotics - Marwansyah Laila (Journal of Law Science, 2021)
Narcotics are needed by humans for treatment so that to meet the needs in the field of medicine and scientific studies, a continuous production of narcotics is needed for these sufferers. On the basis of considering Law Number 35 of 2009 concerning Narcotics, it is stated that narcotics on the one hand are drugs or materials that are useful in the field of treatment or health services and the development of science and on the other hand can also cause dependence which is very detrimental if misused or used without strict control and supervision. The problem in this research is how to tackle and eradicate narcotics crime? What are the efforts of the Medan Police in overcoming and eradicating narcotics crimes? What are the Obstacles in the Countermeasures and Eradication of Narcotics Crimes at the Medan Police? This research is descriptive in nature, which aims to describe exactly what the characteristics of an individual, condition, symptom, or group are, or to determine the spread of a symptom, or to determine whether there is a relationship between a symptom and other symptoms in society. Efforts to overcome and eradicate narcotics crimes within the jurisdiction of the Medan City Police are carried out through non-penal policies and penal policies. Non-penal policies are carried out through preventive and preemptive measures which are implemented through counseling, narcotics safaris, distribution of pamphlets and billboards as well as approaches to traditional and religious leaders as well as community development. This approach was carried out by the Medan City Police Resort in collaboration with BNN and experts through the perspectives of cultural anthropology, sociology, communication, psychology, healthy life education (public health science). The non-penal policy is aimed at children (including school-age youth) and the general public. Penal policies through law enforcement are also applied to police officers who make mistakes in disclosing narcotics cases. Obstacles in overcoming and eradicating narcotics crime in the jurisdiction of the Medan City Police Resort can be viewed from legal factors, law enforcement factors, facilities and facilities in law enforcement, community factors and cultural factors. In general, Law Number 35 of 2009 concerning Narcotics is more comprehensive in regulating the actions that can be taken to uncover narcotics networks. factors of facilities and facilities in law enforcement, community factors and cultural factors. In general, Law Number 35 of 2009 concerning Narcotics is more comprehensive in regulating the actions that can be taken to uncover narcotics networks. factors of facilities and facilities in law enforcement, community factors and cultural factors. In general, Law Number 35 of 2009 concerning Narcotics is more comprehensive in regulating the actions that can be taken to uncover narcotics networks.